High Mobility Field‐Effect Transistors with Versatile Processing from a Small‐Molecule Organic Semiconductor. (2nd April 2013) - Mei, Yaochuan; Loth, Marsha A.; Payne, Marcia; Zhang, Weimin; Smith, Jeremy; Day, Cynthia S.; Parkin, Sean R.; Heeney, Martin; McCulloch, Iain; Anthopoulos, Thomas D.; Anthony, John E.; Jurchescu, Oana D.
<x xml:space="preserve">Abstract</x> Trialkylgermyl functionalization allows the development of high‐performance soluble small‐molecule organic semiconductors with mobilities greater than 5 cm2 V−1 s−1. Spray‐deposited organic thin‐film transistors show a record mobility of 2.2 cm2 V−1 s−1 and demonstrate the potential for incorporation in large‐area, low‐cost electronic applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>